2017
DOI: 10.1007/s10578-017-0774-4
|View full text |Cite
|
Sign up to set email alerts
|

Latent Class Symptom Profiles of Selective Mutism: Identification and Linkage to Temperamental and Social Constructs

Abstract: Selective mutism (SM) is a stable, debilitating psychiatric disorder in which a child fails to speak in most public situations. Considerable debate exists as to the typology of this population, with empirically-based studies pointing to possible dimensions of anxiety, oppositionality, and communication problems, among other aspects. Little work has juxtaposed identified symptom profiles with key temperamental and social constructs often implicated in SM. The present study examined a large, diverse, non-clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 79 publications
0
13
0
1
Order By: Relevance
“…In the latest versions of classification systems such as the DSM (American Psychiatric Association 2013 ) and ICD (World Health Organization 2018 ), SM is categorized as an anxiety disorder. As noted throughout this review, this is justified when looking at the abundant empirical evidence demonstrating that (social) anxiety is a common symptom associated with this psychiatric condition (Driessen et al 2020 ; Cohan et al 2008 ; Diliberto and Kearney 2016 , 2018 ; Schwenck et al 2019 ; Vogel et al 2019 ). The acknowledgement of SM being an anxiety problem is strongly guiding our thinking about the origins of the disorder, which is reflected in developmental psychopathology models that are dominated by anxiety-relevant etiological factors (Cohan et al 2006 ; Muris and Ollendick 2015 ; Viana et al 2009 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the latest versions of classification systems such as the DSM (American Psychiatric Association 2013 ) and ICD (World Health Organization 2018 ), SM is categorized as an anxiety disorder. As noted throughout this review, this is justified when looking at the abundant empirical evidence demonstrating that (social) anxiety is a common symptom associated with this psychiatric condition (Driessen et al 2020 ; Cohan et al 2008 ; Diliberto and Kearney 2016 , 2018 ; Schwenck et al 2019 ; Vogel et al 2019 ). The acknowledgement of SM being an anxiety problem is strongly guiding our thinking about the origins of the disorder, which is reflected in developmental psychopathology models that are dominated by anxiety-relevant etiological factors (Cohan et al 2006 ; Muris and Ollendick 2015 ; Viana et al 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…The second research line indeed relies more on the notion that psychopathological phenomena should be viewed on a continuum and explores to what extent children with SM display varying levels of social anxiety and several other types of symptoms. The aforementioned study by Cohan et al ( 2008 ) is a good example of such an approach, and in general this type of research has shown that although SM is associated with a heterogeneous set of symptoms, social anxiety appears to be a prominent feature that is present in almost all children with this psychiatric condition (see also Diliberto and Kearney 2016 , 2018 ; Schwenck et al 2019 ).…”
Section: Relations Between Sm and Sad/asdmentioning
confidence: 99%
“…Fourth, although this investigation focused on a number of relevant psychopathological and temperamental correlates of SM, it is good to keep in mind that other factors have also been connected to this condition. Prominent examples are developmental delays (Kristensen, 2000), speech and language problems (Manassis et al, 2007), and externalizing symptoms (Diliberto and Kearney, 2018). Thus, in order to get a complete picture of possible antecedents of children's non-speaking behavior, it will be necessary to also include scales or instruments that assess these constructs.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that in most of children, SM is primarily an anxiety-driven condition (Cohan et al, 2008;e.g., Capozzi et al, 2018). However, various scholars have noted out that SM is a heterogeneous disorder (e.g., (Mulligan, 2012)) and that there are children in which-besides (social) anxiety-other problems such as developmental delay (Kristensen, 2000), language expression difficulties (Manassis et al, 2007), oppositional behavior (Diliberto and Kearney, 2018), and presumably ASD or related features are implicated as well.…”
Section: Introductionmentioning
confidence: 99%
“…Diliberto and Kearney ( 2018 ) examined a larger and more diverse sample of children aged 6–10 years identified with selective mutism. Anxiety/distress, oppositionality, and inattention domains were identified via initial exploratory and confirmatory factor analysis.…”
Section: Empirical Clinical Profilesmentioning
confidence: 99%